Troubles with Cognitive Neuroscience - Gabriel Vacariu; Mihai Vacariu (Philosophia Scientiæ)
In few words, we present the main actual problems of cognitive neuroscience: the binding problem, localization, differentiation–integration in the brain, the troubles created by the brain imaging, and optimism vs. skepticism in cognitive neuroscience. Surprisingly, even if there are more and more experimental results in recent years, we notice no real hope for solving these troubles in the future. Cognitive neuroscience is a science constructed on “correlations” between mental and neuronal states, mainly furnished by the brain imaging—fMRI of the last two decades. We want to suggest that “correlation” lacks any ontological background. In this context, we have to answer the following question: Is cognitive neuroscience a real science or a kind of “new engineering”?